2010
DOI: 10.1007/s00253-010-2958-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of co-substrate activation on indigenous and bioaugmented PCB dechlorinating bacterial communities in sediment microcosms

Abstract: Microbial reductive dechlorination by members of the phylum Chloroflexi, including the genus Dehalococcoides, may play an important role in natural detoxification of highly chlorinated environmental pollutants, such as polychlorinated biphenyls (PCBs). Previously, we showed the increase of an indigenous bacterial population belonging to the Pinellas subgroup of Dehalococcoides spp. in Anacostia River sediment (Washington DC, USA) microcosms treated with halogenated co-substrates ("haloprimers"), tetrachloroben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…Other haloprimers such as tetrachlorobenzene (TeCB), pentachloronitrobenzene (PCNB), tetrabromobisphenol A (TBBPA) have resulted in an increase of native PCB dechlorinating bacteria such as Dehalococcoides sp., Ochrobactrum sp., Parasegetibacter sp., Thermithiobacillus sp., Phenylobacterium sp., and Sphingomonas sp. (Krumins et al, 2009;Park et al, 2011;Li et al, 2016). Biostimulation has also been achieved by using electrochemical techniques to treat the PCB contaminated groundwater or sediment (Chun et al, 2013;Yu et al, 2016).…”
Section: Microbial Degradation Of Pcbsmentioning
confidence: 99%
“…Other haloprimers such as tetrachlorobenzene (TeCB), pentachloronitrobenzene (PCNB), tetrabromobisphenol A (TBBPA) have resulted in an increase of native PCB dechlorinating bacteria such as Dehalococcoides sp., Ochrobactrum sp., Parasegetibacter sp., Thermithiobacillus sp., Phenylobacterium sp., and Sphingomonas sp. (Krumins et al, 2009;Park et al, 2011;Li et al, 2016). Biostimulation has also been achieved by using electrochemical techniques to treat the PCB contaminated groundwater or sediment (Chun et al, 2013;Yu et al, 2016).…”
Section: Microbial Degradation Of Pcbsmentioning
confidence: 99%
“…Using halogenated cosubstrates as haloprimers could stimulate anaerobic dechlorination, because certain bacteria can use halogenated co-substrate as a terminal electron acceptor during the respiratory reductive dehalogenation or dehalorespiration process (Hiraishi, 2008). This respiratory activity may play an important role in detoxifying organohalides released into the environment (Park et al, 2011). Based on these past studies, this research explored a number of cosubstrates to assess their effect on TBBPA biodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies suggested that the dechlorination of PCBs was controlled by their sediment geochemical properties and/or microbial species ( Wiegel and Wu, 2000 ; Yan et al, 2006 ; Park et al, 2011 ; Payne et al, 2012 ). This is the first observation of complete dechlorination inhibition in Fe(III)-amended Hudson sediment.…”
Section: Discussionmentioning
confidence: 99%